2009
DOI: 10.1007/s12558-009-0021-4
|View full text |Cite
|
Sign up to set email alerts
|

Cancer du col et VIH en afrique: une revue de la littérature

Abstract: Objectifs : Déterminer la prévalence du cancer du col chez les femmes séropositives au virus de l'immunodéficience humaine (VIH), décrire les déterminants de l'association VIH et cancer du col et faire des recommandations par rapport au dépistage et à la prise en charge du cancer du col chez ces patientes. Méthodologie : Nous avons procédé à une revue non systématique de la littérature de 2004 à 2008 des publications pertinentes, en français ou en anglais sur le cancer du col chez les femmes infectées par le V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In this study, all women were receiving (ARV) therapy, with the majority having restored immunity and a suppressed viral load. This is encouraging because, according to Robinson, ARV treatment may have a positive impact on the progression of cervical lesions in women living with HIV [27]. Furthermore, research has demonstrated that individuals who are HIV+ have an increased risk of abnormal cervical cytology.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, all women were receiving (ARV) therapy, with the majority having restored immunity and a suppressed viral load. This is encouraging because, according to Robinson, ARV treatment may have a positive impact on the progression of cervical lesions in women living with HIV [27]. Furthermore, research has demonstrated that individuals who are HIV+ have an increased risk of abnormal cervical cytology.…”
Section: Discussionmentioning
confidence: 92%